Model pengentasan kemiskinan melalui peran financial inclusion di Indonesia - Firdha Aksari Anindyntha; Dwi Susilowati; Eris Tri Kurniawati (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
The poverty rate in Indonesia is quite high compared to other Asean countries. Indonesia has a poverty rate of 9.8% higher than Thailand and Malaysia. The financial sector through financial inclusion is an alternative policy implemented by the government as an effort to relieve poverty in Indonesia. The fact in Indonesia there is still quite a lot of people who have not been able to access financial services, especially banking sector. This study aims to determine the model of poverty alleviation through the role of financial inclusion in Indonesia. The data analysis technique used PLS-SEM. The results showed that two of three financial inclusion variables, namely access and usage had a significant negative effect on poverty, which means when the role of financial inclusion in Indonesia increases can reduce the poverty in Indonesia. Access variable has a negative effect on poverty which means that increasing public access to debit card ownership, bank accounts, and e-money cards can reduce poverty in Indonesia. Usage variable has a negative effect on poverty which means the increasing use of financial services as reflected with the volume of debit transactions and credit transactions, it can reduce poverty in Indonesia.